1991
DOI: 10.1002/pssa.2211280207
|View full text |Cite
|
Sign up to set email alerts
|

Electron Microscopy of Dislocation Structures in SrTiO3 Deformed at High Temperatures

Abstract: Dislocations in SrTiO3 deformed plastically by indentation at 900 and 1100 °C are studied by comprehensive transmission electron microscopy. At both 900 and 1100°C all the dislocations studied have Burgers vectors of either 〈100〉 or 〈110〉 type. At 900 °C both types of dislocation are in the glide configuration. On the other hand, at 1100°C 〈001〉 dislocations are in the climb configuration, although most of 〈110〉 dislocations are in the glide configuration. Small dislocation loops, both of 〈100〉 and 〈110〉 types… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
15
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(17 citation statements)
references
References 9 publications
2
15
0
Order By: Relevance
“…In the following, the pseudo-cubic setting will be referred by the subscript "c" while no indication will be given when the actual orthorhombic symmetry will be used. Transformations from cubic to orthorhombic (Pbnm) or orthorhombic to cubic directions are given by: (Doukhan & Doukhan 1986;Wright et al 1992, Besson et al 1996, BaTiO 3 (Doukhan & Doukhan 1986;Lin & Lu 2002), SrTiO 3 (Nishigaki et al 1991, Wang et al 1993, Mao & Knowles 1996, Matsunaga & Saka 2000Brunner et al 2001;Gumbsch et al 2001;Zhang et al 2002a, b;Jia et al 2005) { } c family.…”
Section: Structure and Possible Dislocationsmentioning
confidence: 99%
“…In the following, the pseudo-cubic setting will be referred by the subscript "c" while no indication will be given when the actual orthorhombic symmetry will be used. Transformations from cubic to orthorhombic (Pbnm) or orthorhombic to cubic directions are given by: (Doukhan & Doukhan 1986;Wright et al 1992, Besson et al 1996, BaTiO 3 (Doukhan & Doukhan 1986;Lin & Lu 2002), SrTiO 3 (Nishigaki et al 1991, Wang et al 1993, Mao & Knowles 1996, Matsunaga & Saka 2000Brunner et al 2001;Gumbsch et al 2001;Zhang et al 2002a, b;Jia et al 2005) { } c family.…”
Section: Structure and Possible Dislocationsmentioning
confidence: 99%
“…The nature of dislocations has been studied so far by using transmission electron microscopy (TEM). [10][11][12][13] Dislocations in SrTiO 3 have a Burgers vector of either h100i or h110i type depending on the deformation condition. It was reported that the grown-in dislocations have a Burgers vector of h100i type, while the dislocations introduced during plastic deformation at room temperature have a Burgers vector of h110i type.…”
mentioning
confidence: 99%
“…As generally observed in perovskites, 2 the most common slip systems observed in deformed SrTiO 3 are ͗110͕͘110͖ and ͗100͕͘010͖. [3][4][5][6] It is, however, possible, following elaboration, to find other dislocation types such as ͗110͕͘001͖ 7 or ͗001͕͘110͖. 8 The plasticity of SrTiO 3 exhibits a very surprising evolution with temperature with a very strong flow stress anomaly eventually leading to an inverse brittle-ductile transition.…”
Section: Introductionmentioning
confidence: 95%
“…It is also widely used as a substrate for the epitaxial growth of high-temperature superconducting ͑and many oxides͒ thin films, for special optical windows, and as high quality sputtering target. For these reasons, several studies have addressed recently the issue of plastic deformation and dislocation properties in SrTiO 3 . As generally observed in perovskites, 2 the most common slip systems observed in deformed SrTiO 3 are ͗110͕͘110͖ and ͗100͕͘010͖.…”
Section: Introductionmentioning
confidence: 99%